Analisis Indeks Glikemik dan Beban Glikemik Inovasi Sport Food Bolu Kukus dari Tepung Biji Kecipir (Psophocarpus tetragonolobus. L) dan Tepung Pati Garut (Maranta arundinaceae. L): Glycemic Index and Glycemic Load of a Steamed Sponge Cake Developed as a Novel Sport Food from Winged Bean (Psophocarpus tetragonolobus L.) Seed Flour and Arrowroot (Maranta arundinacea L.) Starch - Tennesa Sheryan Nela Fernanda; Nanang Nasrulloh (Amerta Nutrition, 2025)
Background: Proper nutrition supports athlete performance and recovery. Winged bean seed flour provides protein, while Arrowroot starch contains amylose and amylopectin and is easily digestible Their combination in a steamed sponge cake may provide complex carbohydrates and fiber that help regulate glycemic index and glycemic load, providing stable and sustained energy. Objectives: This study aimed to evaluate the glycaemic index (GI) and glycaemic load (GL) of steamed sponge cake formulated from winged bean seed flour and arrowroot starch as an innovation in sports nutrition. Methods: In vitro and in vivo experimental methods were applied to three formulations of steamed sponge cake: F1 (25:75), F2 (50:50), and F3 (75:25) ratios of winged bean flour to arrowroot starch. To measure the glycemic index and glycemic load in 10 students from UPN “Veteran” Jakarta, participants were given two test meals (pure glucose and steamed sponge cake), each containing 25 g of carbohydrates. Peripheral blood glucose was measured at 0, 15, 30, 45, 60, 90, and 120 minutes after a 10-hour fast using a glucometer. GI and GL were calculated based on the area under the blood glucose response curve (AUC). Results: The glycemic index values of the steamed cakes were 79 (F1), 68.5 (F2), and 49.3 (F3), and were categorized as having a moderate glycemic index. Conclusions: Steamed sponge cake formulated from winged bean flour and arrowroot starch shows potential as a sports food due to its favorable glycaemic characteristics for athletes.